Influence of allowable interruption period on estimates of accelerometer wear time and sedentary time in older adults - Mailey, Emily L.; Gothe, Neha P.; Wójcicki, Thomas R.; Szabo, Amanda N.; Olson, Erin A.; Mullen, Sean P.; Fanning, Jason T.; Motl, Robert W.; McAuley, Edward (My University, 2014)
The criteria one uses to reduce accelerometer data can profoundly influence the interpretation of research outcomes. The purpose of this study was to examine the influence of three different interruption periods (i.e., 20, 30, and 60 minutes) on the amount of data retained for analyses and estimates of sedentary time among older adults. Older adults (N=311; M[subscript age]=71.1) wore an accelerometer for seven days and reported wear time on an accelerometer log. Accelerometer data were downloaded and scored using 20, 30, and 60-minute interruption periods. Estimates of wear time derived using each interruption period were compared to self-reported wear time, and descriptive statistics were used to compare estimates of sedentary time. Results showed a longer interruption period (i.e., 60 minutes) yields the largest sample size and the closest approximation of self-reported wear time. A short interruption period (i.e., 20 minutes) is likely to underestimate sedentary time among older adults.
Keywords: Accelerometer wear; Interruption periods; Sedentary time; Older adults